CPLP of the Sea: Towards a Lusophone Maritime Spatial Data Infrastructure (LMSDI) - Ugeda, Luiz; Sanches, Karine (European Spatial Research and Policy, 2025)
This article explores the potential of a Lusophone Maritime Spatial Data Infrastructure (LMSDI) to enhance geospatial cooperation among Portuguese-speaking countries. Grounded in bibliographic and documentary analysis, the study examines how shared oceanic heritage and spatial data interoperability can support marine governance across the CPLP. It proposes the development of a Lusophone Geoportal for monitoring Exclusive Economic Zones, promoting environmental enforcement, and advancing the blue economy through digital integration and multilateral collaboration.